Processing, characterization and properties of novel gradient Si3N4/SiC fibers derived from polycarbosilanes. Issue 13 (October 2019) - Dong, Xichao; Guo, Changqing; Liu, Xingyu; Gu, Chong; Wu, Pengfei; Lin, Wen; Lu, Yingxi; Su, Zhiming; Yu, Zhaoju; Liu, Anhua
Abstract: In this work, we report a novel kind of Si3 N4 /SiC composite fibers, which exhibit a controlled gradient Si3 N4 (shell)/SiC(core) structure. These composite fibers are fabricated through a controlled nitridation and pyrolysis process on electron irradiation-cured polycarbosilane fibers. Structural and chemical analysis based on Elemental Analyzer, FT-IR, Raman spectroscopy, electron probe micro-analyzer, X-ray photoelectron spectroscopy, and X-ray diffraction confirm the gradient structure of obtained fibers, which consist a shell with high Si3 N4 content and a SiC core. The as-fabricated fibers exhibit dense and smooth surfaces, and no microscopic holes or defects were observed. The effects of nitridation temperature on mechanical properties and electrical resistivity were also investigated. Combined with high mechanical properties and lightweight, the present gradient Si3 N4 /SiC fibers open a new strategy to fabricate multifunctional and electromagnetic wave absorbing materials.